Arterial Injury and Endothelial Repair: Rapid Recovery of Function after Mechanical Injury in Healthy Volunteers. (28th January 2014) - Tilling, Lindsey; Hunt, Joanne; Donald, Ann; Clapp, Brian; Chowienczyk, Phil
Abstract : Objective . Previous studies suggest a protracted course of recovery after mechanical endothelial injury; confounders may include degree of injury and concomitant endothelial dysfunction. We sought to define the time course of endothelial function recovery using flow-mediated dilation (FMD), after ischaemia-reperfusion (IR) and mechanical injury in patients and healthy volunteers. The contribution of circulating CD133 + /CD34 + /VEGFR2 + "endothelial progenitor" (EPC) or repair cells to endothelial repair was also examined. Methods . 28 healthy volunteers aged 18–35 years underwent transient forearm ischaemia induced by cuff inflation around the proximal biceps and radial artery mechanical injury induced by inserting a wire through a cannula. A more severe mechanical injury was induced using an arterial sheath and catheter inserted into the radial artery of 18 patients undergoing angiography. Results . IR and mechanical injury produced immediate impairment of FMD (from 6.5 ± 1.2% to 2.9 ± 2.2% and from 7.4 ± 2.3% to 1.5 ± 1.6% for IR and injury, resp., eachP < 0.001 ) but recovered within 6 hours and 2 days, respectively. FMD took up to 4 months to recover in patients. Circulating EPC did not change significantly during the injury/recovery period in all subjects. Conclusions . Recovery of endothelial function after IR and mechanical injury is rapid and not associated with a change in circulating EPC.